The Glycolytic Pathway is the Predominate Path for Glucose Utilization in Human Pancreatic Beta Cells (1.1B4) - Hisab, Ahmed S.; Alahmed, Jala A S (European Scientific Journal, ESJ, 2018)
The oxidative metabolism of energy substrates has a paramount role in the stimulus secretion pathway of insulin. However, the role of glycolytic pathway in pancreatic beta cells is not very well understood. To address this, we have investigated and compared the functional effects of two mitochondrial substrates (glucose and Î±-ketoisocaproate) between the human (1.1B4) and murine (MIN6) pancreatic beta cell lines. MTS assay was conducted as an indicator of the metabolic activity of both cell lines. Polarographic detection of (Î”O2) and lactate were used to measure the oxygen consumption rate and anaerobic glycolysis respectively. The mitochondrial redox state was monitored via RH123 distribution and NAD(P)H autofluorescence. The metabolic assays showed glucose stimulated MTS reduction in MIN6 cells in a time and concentration dependent manner and nor in 1.1B4. Both sub strates failed to affect OCR, NADPH and increased lactate production in 1.1B4 cells. However, they stimulated OCR, increased NADPH, increased lactate output but was less extent and hyperpolarized the mitochondria in MIN6 cells. The above results showed that 1.1B4 cells are mainly depending on the glycolytic pathway different from MIN6 cells which rely on mitochondrial respiration. In conclusion, 1.1B4 cell line represents a new model to study the bioenergetics profile because it depends on the anaerobic glycolysis rather than aerobic respiration of the other models such as MIN6 and islets.